Peter Singer’s Speciesist Notion of Animal Conservation Vis-a-Vis Genetic Manipulation - Ncha, Gabriel Bubu; Etta, Emmanuel E.; Ojong, Lawrence Odey (Studia Ecologiae et Bioethicae, 2025)
This paper shows how human activity through genetic engineering causes pain to non-human animals. It primarily deals with an evaluation of the phenomenon of animal rights (specifically animal conservation) from the view of Singer’s notion of speciesism. Singer’s notion of speciesism frowns at all forms of animal maltreatment and emphasizes that animals are sentients, and they are capable of suffering and feeling pain. The central problem here is whether animal’s life has intrinsic value and whether they can be used for experiment. Among the several ways by which speciesism is practiced, this work identified genetic engineering as a major obstacle to animal conservation because humans will invade the animal space to look for various animal species to carry out experiment on. Using the method of critical analysis, evaluation and prescription, the paper argues that animals have life and belong to the environment and as such, the environment should be conserved also for their sake and if humans continue to exploit the environment by using animals for genetic manipulations, there will be negative consequences to humans and extinction of some species.